Mutation rate and novel tt mutants of Arabidopsis thaliana induced by carbon ions. - Shikazono, Naoya (2003)
Irradiation of Arabidopsis thaliana by carbon ions was carried out to investigate the mutational effect of ion particles in higher plants. Frequencies of embryonic lethals and chlorophyll-deficient mutants were found to be significantly higher after carbon-ion irradiation than after electron irradiation (11-fold and 7.8-fold per unit dose, respectively). To estimate the mutation rate of carbon ions, mutants with no pigments on leaves and stems (tt) and no trichomes on leaves (gl) were isolated at the M2 generation and subjected to analysis. Averaged segregation rate of the backcrossed mutants was 0.25, which suggested that large deletions reducing the viability of the gametophytes were not transmitted, if generated, in most cases. During the isolation of mutants, two new classes of flavonoid mutants (tt18, tt19) were isolated from carbon-ion-mutagenized M2 plants. From PCR and sequence analysis, two of the three tt18 mutant alleles were found to have a small deletion within the LDOX gene and the other was revealed to contain a rearrangement. Using the segregation rates, the mutation rate of carbon ions was estimated to be 17-fold higher than that of electrons. The isolation of novel mutants and the high mutation rate suggest that ion particles can be used as a valuable mutagen for plant genetics.